Left atrial myxoma: new perspectives in the diagnosis of murmur free cases. Issue 6 (December 1986) - Nihoyannopoulos, P; Venkatesan, P; David, J; Hackett, D; Valantine, H; Oakley, C M
Abstract : No cardiological signs or symptoms were seen in three patients with left atrial myxomas. The diagnosis was established by cross sectional echocardiography. In two patients this investigation was performed to exclude a cardiac source of systemic emboli. The third patient had constitutional signs only. All three had raised erythrocyte sedimentation rates and C reactive protein concentrations. In two patients the myxomas were successfully excised; the third patient who had presented with massive peripheral and central embolisation died during emergency operation. Cross sectional echocardiography is the technique of choice for detecting atrial myxomas and the absence of the cardiological signs should not preclude referral for diagnostic echocardiography.